(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The Dobbs v. Jackson Women’s Health Organization has made extensive use of the originalist canon to overrule two historical Supreme Court precedents recognizing the right to abortion. The article analyzes its arguments, highlighting their contradictions and criticizing the general conception of the Constitution sketched by the decision.